Cable health degradation V: cable health degradation monitoring & analysis using insulation resistance - Loh, Shu Zhen (Nanyang Technological University, 2022)
As technology advances along the years, the use of electricity serves an important role in our day-to-day life. Electrical cables play an essential part of providing electricity for consumers, enabling people to receive power for domestic or commercial use. Cables are dominantly used in many applications, such as our usual daily use items like handphone, or even large cables that transmit power to supply for large scale operations. Therefore, the significance of cable health is important for us to monitor anything that requires power consumption. To determine the health of a cable, an insulation resistance test will be conducted to assess the condition of cable. This is a commonly used method to measure resistance measured between two points to give a gauge of the cable working condition. This raises a concern whereby a simple insulation resistance test will not be sufficient to provide a more comprehensive analysis of a cable health as there are many factors that will affect a cable health, not solely the insulation. This project proposes to develop a GUI (Graphical User Interface) Application that will analyze data obtained from an insulation resistance testing device and determine the health condition of a cable. In this report, only the electrical properties of the cable health will be discussed.